Gender dimensions of community-based groundwater governance in Ethiopia: using citizen science as an entry point - Nigussie, Likimyelesh (International Water Management Institute, 2018)
Presented by Likimyelesh Nigussie (IWMI), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.